LAND USE PLANNING FOR SETTLEMENTS AREA IN CONSIDERATION OF FLOOD AND LANDSLIDE HAZARDS IN BAGELEN SUB-DISTRICT, PURWOREJO INDONESIA - Estuning Tyas Wulan Mey; Sudibyakto Sudibyakto; Nanette C. Kingma (Indonesian Journal of Geography, 2009)
The objective of this research is  determining alternative land use for settlement development considering  its hazards susceptibility.  Data were obtained by interviews, participatory GIS, direct-observation, sampling of soil  and secondary data analysis. The flood hazard map was produced using Kriging interpolation techniques; flood depth map for the largest flood in the year 2004 was created. The area with high landslide hazard is located on the hilly area in the eastern part of the area of study. The result from overlaying two hazard maps indicates that the area which considered as having less hazards  is located on the colluvial plain. The result of suitability analysis including hazard and people perception-based criteria showed that the area suitable is mostly located in Bagelen and Krendetan Villages. The result of suitability analysis of the non-hazard criteria showed that the area suitable  of which 338.1 Ha is an existing settlement.